1888. Clinicians' Beliefs, Knowledge, Attitudes, and Planned Behaviors on Antibiotic Prescribing in Acute Respiratory Infections. (26th November 2018) - Hruza, Hayli; Velasquez, Tania; Madaras-Kelly, Karl; Fleming-Dutra, Katherine; Samore, Matthew; Butler, Jorie
Abstract: Background: We sought to gauge provider perceptions to prepare an intervention which featured audit-feedback reports, academic detailing, and communication training to improve antibiotic treatment of acute respiratory infections (ARIs). Methods: One-on-one interviews with providers ( n = 20) from five VA Medical Centers were conducted in May–July 2017. Participants were recruited from emergency departments, primary care and community-based outreach clinics by e-mail. Interviews were conducted by telephone, audio-recorded, and transcribed. The Theory of Planned Behavior was used to develop semi-structured interview questions to capture attitudes, subjective norms (peer practices), planned future behaviors for managing ARIs, and intervention tools. Interviews were analyzed using codes developed from participant responses and categorized via consensus among authors. Codes were categorized into themes to map mental models. Results: Beliefs and Attitudes: Providers were open to audit-feedback and tools to improve prescribing practices. Barriers to appropriate prescribing were perceived to include patient demand, time and resource limitations. Unfamiliarity with receipt of personal feedback and undefined roles of personnel to provide feedback within the clinic were anticipated to impede successful implementation. Behavior Control: Providers felt they had control to withhold or prescribe antibiotics. Social norms: Peer practices and lack of patient knowledge were perceived to drive patient demand. Planned future behaviors: The use of audit-feedback and communication strategies to address perceived patient demand were viable solutions to improve prescribing practices. However, utility of Shared Decision Making as a strategy varied due to provider expertise that antibiotics were not indicated for most ARIs; patient gaps in knowledge; and perceived patient insistence for an antibiotic. Conclusion: Providers often intend to prescribe antibiotics appropriately yet barriers can influence practice. Potential interventions should provide tailored audit-feedback, address perceived patient demand, and support clinic structure to provide feedback. Strategies should consider time and resources available to address barriers. Disclosures: All authors: No reported disclosures.